Telehealth - Heston, Thomas F. (IntechOpen, 2019)
The practice of telemedicine enables the remote practice of medicine across a wide spectrum of medical specialties, from radiology to psychiatry and intensive care. Progressing from the telegraph to telephone, to video and to remote-sensing devices, telemedicine now brings specialty medical care to all regions of the global community. Telemedicine research now includes investigation into optimal data transmission and legislative issues, in addition to the development of improved medical devices. This collection of the latest thinking by experts in the telemedicine field will help readers stay abreast of the latest developments in this important field of medicine.